Composite current collector and preparation method thereof, battery and electric equipment

By detecting pinholes after the metal film layer of composite fluid collecting and spraying and filling conductive slurry, the pinhole problem on the surface of composite fluid collecting is directly repaired, and the problem of limited pinhole improvement effect in the prior art is solved, and the improvement of the pinhole improvement effect is improved. Product stability and consistency.

CN119230840APending Publication Date: 2024-12-31NAXAU NEW MATERIALS CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411340869.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing composite liquid collector often has pinhole problems in coating processes, resulting in a decrease in the mechanical properties of the base film and unstable operation in the electrolyte. The existing solutions can only be processed before the metal film layer is formed, and the effect is limited and cannot be completely eliminated. The pinhole has been formed.

Method used

After the metal film layer is formed, the pinhole is directly repaired by pinhole detection and spraying filling of conductive slurry, and the pinhole is filled with conductive slurry composed of polymer materials and conductive particles, and a repair layer is formed by drying to ensure the surface of the composite fluid collection. smooth.

Benefits of technology

It effectively eliminates the pinhole problem on the surface of the composite fluid collecting, improves the product yield and safety, and does not affect other performance, has high production efficiency and good product consistency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230840A_ABST
    Figure CN119230840A_ABST
Patent Text Reader

Abstract

The invention provides a composite current collector and a preparation method thereof, a battery and electric equipment, and relates to the technical field of lithium ion batteries, the composite current collector is characterized in that a metal layer is formed on the surface of a polymer material layer, pinholes in the surface of the composite current collector are detected by CCD online monitoring equipment, and the pinholes are filled with conductive slurry to form the pinhole-free composite current collector. The defect that pinholes easily appear on the surface of the composite current collector is overcome. The invention also provides the composite current collector prepared based on the method, and a lithium ion battery and electric equipment based on the composite current collector. According to the technical scheme provided by the invention, the problem that pinholes in the surface of the composite current collector are difficult to avoid in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a composite current collector and a preparation method thereof, a battery, and an electrical device. Background Art

[0002] In the lithium battery industry, the emerging composite current collector has obvious advantages over the traditional metal current collector. It uses polymer materials such as PET / PP as the base film, and deposits copper / aluminum conductive layers on both sides through vacuum coating, electroplating and other processes to form a composite material, forming a "metal-polymer material-metal" "sandwich" structure. It transmits electrons between the positive and negative electrodes of the battery, thereby realizing the battery's charge and discharge process. However, the surface of the composite current collector often has the undesirable phenomenon of pinholes after coating, which is usually caused by the low heat resistance of the base film or the high energy of the metal particles. This not only affects the mechanical properties of the base film, but also affects the subsequent operation stability of the base film in the electrolyte.

[0003] The existing solutions are mainly to reduce the generation of pinholes by improving the coating process. Chinese patent CN219972449U adopts magnetron sputtering + water electroplating, and vacuum heating before coating to remove water vapor on the PET film, effectively avoiding the generation of pinholes after the PET film is coated. However, this method can only solve the problem of poor adhesion of metal particles due to the presence of original water vapor. Chinese patent CN116351610A adopts a coating process to prepare a composite current collector, and the current collector is pre-treated by "pre-wetting" and "micro-etching" before coating, which helps to improve pinholes, bubbles and other defects and improve the yield of the coating process. The above methods are all helpful in improving pinholes, but these pinhole improvement processes are all processed before the metal film layer is formed, and there are many factors that form pinholes, so the improvement effect is limited, and it is difficult to eliminate the formed pinholes. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a composite current collector, which can directly eliminate pinholes after the metal film layer is formed, thereby improving the problem that the pinholes in the prior art can only be reduced indirectly by improving the process or raw materials before the metal film layer is formed, resulting in limited pinhole reduction effect and unstable pinhole quality in the product.

[0005] Another object of the present invention is to provide a composite current collector.

[0006] Another object of the present invention is to provide a battery.

[0007] Another object of the present invention is to provide an electrical device.

[0008] In a first aspect, the present application provides a method for preparing a composite current collector, comprising the following steps:

[0009] Providing a current collector including a resin film layer and a metal film layer;

[0010] Inspect the surface of the current collector and mark the location of the pinholes;

[0011] According to the marked positions of the pinholes, the conductive slurry is sprayed and filled, the surface of the current collector is leveled, and the current collector is dried to obtain a composite current collector.

[0012] Furthermore, in some embodiments of the present application, the viscosity of the conductive slurry is not higher than 1000 cP, and the conductivity is not lower than 1 S / cm.

[0013] Furthermore, in some embodiments of the present application, the conductive slurry includes a polymer substance and conductive particles, and the polymer substance is at least one of the resin in the resin film layer and its derivatives.

[0014] Furthermore, in some embodiments of the present application, the conductive particles are at least one of metals, conductive compounds of metals, graphene, carbon nanotubes, and conductive polymer materials.

[0015] Furthermore, in some embodiments of the present application, the particle size of the conductive particles is D90≤10nm, and the specific surface area is ≥2m 2 / g.

[0016] Furthermore, in some embodiments of the present application, the conductive slurry also includes at least one of pure water, a dispersant, and a wetting agent.

[0017] Furthermore, in some embodiments of the present application, the pure water accounts for 0 to 30% by mass in the conductive slurry.

[0018] Furthermore, in some embodiments of the present application, the proportion of the dispersant in the conductive slurry is 0-5% by mass.

[0019] Furthermore, in some embodiments of the present application, the wetting agent accounts for 0 to 5% by mass in the conductive slurry.

[0020] Furthermore, in some embodiments of the present application, the polymer substance accounts for 50-60% by mass in the conductive slurry.

[0021] Furthermore, in some embodiments of the present application, the conductive particles account for 0.1 to 15% by mass in the conductive slurry.

[0022] Furthermore, in some embodiments of the present application, the pure water is pure water with a conductivity of less than 20 μS / cm.

[0023] Furthermore, in some embodiments of the present application, the dispersant is an anionic surfactant or a cationic surfactant.

[0024] Furthermore, in some embodiments of the present application, the wetting agent is at least one of a fatty acid wetting agent, an aliphatic amide wetting agent, and a lipid wetting agent.

[0025] Furthermore, in some embodiments of the present application, during spraying, the conductive slurry is directly opposite the marked pinhole, the spraying pressure of the conductive slurry is 0.1-0.5 MPa, and the vertical distance between the nozzle and the metal film layer is 150-300 mm.

[0026] Furthermore, in some embodiments of the present application, the spraying of the conductive slurry is intermittent spraying, and the single spraying amount is not higher than 0.5 ml.

[0027] Further, in some embodiments of the present application, the leveling of the current collector surface includes: using a scraper to evenly spread the conductive slurry on the current collector surface;

[0028] The angle between the blade of the scraper and the advancing direction of the current collector is greater than 90°.

[0029] Furthermore, in some embodiments of the present application, any one of a fluorescent agent, a colorant, and a dye is used to mark the pinhole position.

[0030] Furthermore, in some embodiments of the present application, CCD is used in the pinhole detection process to detect pinholes on the surface of the current collector online.

[0031] In a second aspect, the present application further provides a composite current collector, comprising a resin film layer and metal film layers respectively located on both sides of the resin film layer;

[0032] The metal film layer is partially or entirely covered with a repair layer;

[0033] The repair layer includes a polymer substance and conductive particles distributed in the polymer substance;

[0034] The polymer substance is the same as the resin in the resin film layer or is a derivative of the resin in the resin film layer;

[0035] The conductive particles account for 0.1-15% by mass in the repair layer.

[0036] Furthermore, in some embodiments of the present application, the conductive particles are at least one of metal, conductive compound of metal, graphene, carbon nanotube, and conductive polymer material; and / or

[0037] The particle size of the conductive particles is D90≤10nm, and the specific surface area is ≥2m 2 / g.

[0038] Furthermore, in some embodiments of the present application, the thickness of the resin film layer is ≤100 μm; and the thickness of the metal film layer is ≤10 μm.

[0039] Furthermore, in some embodiments of the present application, the pinholes on the surface of the composite current collector are no larger than 5 μm.

[0040] Furthermore, in some embodiments of the present application, the composite current collector is prepared by the above-mentioned composite current collector preparation method.

[0041] In a third aspect, the present application further provides a battery, comprising a negative electrode and a composite current collector, wherein the composite current collector is a composite current collector prepared by the method for preparing the composite current collector described in the first aspect or the composite current collector described in the second aspect.

[0042] In a fourth aspect, the present application also provides an electrical device, comprising the battery described in the third aspect.

[0043] The embodiment of the present application provides a composite current collector and its preparation method, battery, and electrical equipment. After the composite current collector is prepared to form a "sandwich" type composite current collector, the surface of the current collector is tested for pinholes, and the pinholes are filled with conductive slurry according to the test results to avoid the presence of pinholes on the surface of the composite current collector, which solves the problem that the pinholes on the composite current collector in the prior art can only be indirectly improved by adjusting the process before the metal film layer is formed and the process during the formation of the metal film layer, and the improvement effect is limited, and the pinholes that have been formed on the composite current collector cannot be solved. The preparation method of the composite current collector provided by the present application effectively solves the undesirable phenomenon of pinholes on the surface of the composite current collector, does not affect other properties of the composite current collector, and improves the yield and safety of the composite current collector; in addition, the preparation method is simple and easy to implement, has high production efficiency, good product consistency, and is easy to produce and promote.

[0044] The composite current collector provided in the present application has no pinholes with a diameter greater than 5 μm and has excellent other properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 A schematic diagram of the system structure used for the preparation method provided in this application.

[0046] Among them, 10-detection equipment, 20-marking equipment, 30-spraying equipment, 40-leveling equipment; 50-drying equipment, 60-cooling equipment, 70-winding equipment, 110-current collector. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The composite current collector is a battery current collector material with a sandwich structure similar to a "sandwich", in which the middle layer is a plastic film made of polymer insulating resin, and metal layers of nanometer to submicron scale, such as metal copper layer and metal aluminum layer, are formed on both sides of the plastic film. Among them, the metal layer is formed on the surface of the middle layer mainly by chemical deposition, magnetron sputtering, vacuum evaporation, electroplating and other methods, but due to the low heat resistance of the base film or the high energy of the metal particles, pinholes and other undesirable conditions will appear during the production process, which will not only affect the mechanical properties of the base film, but also affect the subsequent operation stability of the base film in the electrolyte. Therefore, in order to solve this technical problem, a variety of solutions have been proposed in the prior art, such as using two-step and three-step methods to thicken the metal layer; adding a bonding layer between the resin film layer and the metal layer and optimizing the process parameters. However, these methods are to prevent or reduce the occurrence of pinholes before the pinholes are formed, and they cannot avoid the formation of pinholes. And there is currently no solution for the pinholes that have already formed.

[0049] On this basis, the applicant provides a method for preparing a composite current collector to solve this technical problem. After a metal layer is deposited on a resin film layer to obtain a composite current collector, a pinhole detection process and a pinhole repair process are added to perform positioning repair on the pinholes formed on the surface of the current collector, thereby solving the pinhole problem of the composite current collector. The method specifically includes the following steps:

[0050] Pinhole detection process and pinhole repair process;

[0051] The pinhole detection process comprises: detecting pinholes on the surface of the current collector and marking the pinhole positions;

[0052] The pinhole repairing process comprises spraying and filling a conductive slurry according to the marked pinhole position, flattening the surface of the current collector, and drying to obtain a composite current collector.

[0053] Among them, the material and thickness of the resin film layer of the composite current collector are not limited in this application. It can be any resin film layer that meets the requirements of the composite current collector, such as PET, PP; its thickness can also be adjusted according to the requirements; the material and thickness of the metal film layer are not limited in this application. It can be any metal film layer that meets the requirements of the composite current collector, such as copper, aluminum; in addition, the process of forming the metal film layer on the resin film layer is not limited in this application. It can be formed by a one-step method, such as chemical deposition, magnetron sputtering, or by a two-step method, such as magnetron sputtering + electroplating, or by a three-step method, such as magnetron sputtering + vacuum evaporation + electroplating. The thickness of the metal film layer formed can be nanometer-level thickness or submicron-level thickness. For example, the thickness of the metal film layer of this application can be 10nm~2μm.

[0054] The pinhole detection method may be any method that can continuously check whether there are pinholes on the surface of the composite current collector, such as CCD detection equipment; the measurable width of the CCD online detection equipment is 500 to 2500 mm, and the detection accuracy needs to be 0.01 to 0.1 mm / pixel.

[0055] Furthermore, during the detection process, the composite current collector is continuously conveyed under the drive of the conveying roller, so as to realize continuous detection, marking, spraying and filling pinholes of the composite current collector, realize continuous production, and improve production efficiency and consistency of product quality.

[0056] Among them, in the process of marking, the marker used can be any one of a fluorescent agent, a colorant, and a dye, which is used to mark the position of the pinhole. The marking range is larger than the pinhole range. When filling, the filled conductive slurry completely covers the marker, and the pinhole is completely filled. The marking range should not be too large to avoid too much conductive slurry being sprayed on the composite current collector. Exemplarily, in the marking process, the marker forms a circle to circle the position of the pinhole. At this time, the diameter of the circle formed by the marker is larger than the diameter of the pinhole (the maximum width of the pinhole on the current collector), such as 1.2 to 1.5 times the diameter of the pinhole, which is used to indicate the range of conductive slurry filling.

[0057] In some embodiments, the viscosity of the conductive slurry is not higher than 1000 cP, and the conductivity is not lower than 1 S / cm, so as to ensure that the material used for spray filling has little effect on the electrical properties of the composite current collector. Preferably, the viscosity of the conductive slurry is not higher than 200 cP, and the conductivity is not lower than 2 S / cm.

[0058] In order to increase the adhesion between the conductive slurry and the composite current collector, the conductive slurry generally includes a polymer substance for providing adhesion and improving the dispersion effect and conductive particles for providing conductive properties. Preferably, the polymer substance adopts at least one of the resin in the resin film layer and its derivatives. For example, when the material of the resin film layer is PET, the polymer substance in the conductive slurry can also be PET or a derivative of PET. Among them, the PET or the derivative of PET in the polymer substance here should be understood as a compound that is the same as the PET in the resin film layer or has the same skeleton or the same active group as the PET in the resin film layer, or a polymer substance that can undergo a condensation reaction with the PET in the resin film layer, or a compound with a polarity similar to that of the PET in the resin film layer, so as to improve the bonding force between the conductive slurry and the resin film layer, so that the filled conductive slurry can better adhere to the resin film layer.

[0059] The conductive particles may be any conductive material that has conductive properties and does not chemically react with the metal film layer at room temperature or operating temperature, such as at least one of metal, conductive compound of metal, graphene, carbon nanotube, and conductive polymer material. For example, the metal may be silver, copper, aluminum, nickel, and conductive compounds thereof.

[0060] The particle size of the conductive particles is D90≤10nm, and the specific surface area (BET) is ≥2m 2 / g, where D90 is the particle size corresponding to 90% of the cumulative distribution in the system; the specific surface area (BET) represents the total area per unit mass of the material. Preferably, the particle size of the conductive particles is D90 ≤ 5nm, and the specific surface area (BET) ≥ 5m 2 / g.

[0061] The conductive particles may be in any shape, such as spherical, quasi-spherical, porous particles, or tubular. Porous particles with rough surfaces are preferred, as they can increase the specific surface area, improve the overall strength, and viscosity.

[0062] In order to further improve the dispersibility of the conductive particles in the conductive slurry, a dispersant and / or a wetting agent may be added to the conductive slurry to improve the dispersion of the conductive particles in the conductive slurry and avoid agglomeration. In addition, pure water may be added to the conductive slurry to adjust the viscosity of the conductive slurry.

[0063] However, the proportion of the pure water in the conductive slurry should not be too high, preferably 0 to 30% by mass, and more preferably 0 to 25% by mass.

[0064] In some embodiments, the proportion of the dispersant in the conductive slurry is 0-5% by mass. The proportion of the wetting agent in the conductive slurry is 0-5% by mass. Preferably, the proportion of the dispersant in the conductive slurry is 0-3% by mass; the proportion of the wetting agent in the conductive slurry is 0-3% by mass.

[0065] The polymer substance accounts for 50-60% by mass in the conductive paste.

[0066] In some embodiments, the conductive particles account for 0.1-15% by mass in the conductive slurry, preferably 5%-15% by mass.

[0067] When pure water is added to the conductive slurry, the pure water should have a conductivity of less than 20 μS / cm to reduce the influence of free ions in the water on the composite current collector.

[0068] In some embodiments, the dispersant is an anionic surfactant, such as sodium dodecylbenzene sulfonate or a cationic surfactant, such as hexadecyltrimethylammonium bromide, or a chelating agent, such as EDTA.

[0069] In some embodiments, the wetting agent is at least one of a fatty acid wetting agent, such as polyglycerol fatty acid ester (PGE), ethoxylated fatty acid methyl ester (MEE), etc.; an aliphatic amide wetting agent, such as fatty acid diethanolamide sulfate sodium salt (DFMS); an ester wetting agent, such as diglyceride, etc.

[0070] In the pinhole repair process, the conductive slurry is directly opposite to the marked pinhole, the spraying pressure of the conductive slurry is 0.1-0.5MPa, and the vertical distance between the nozzle and the metal film layer is 150-300mm. Preferably, the spraying pressure of the conductive slurry is 0.1-0.5MPa, and the vertical distance between the nozzle and the metal film layer is 150-300mm. In the present application, the spraying pressure of the conductive slurry should not be too high or too low. Too high spraying pressure can easily cause damage to the metal film layer, while too low spraying pressure may cause insufficient atomization of the slurry, and the repair film formed on the base film is not smooth and rough. The vertical distance between the nozzle and the metal film layer should not be too high or too low, because if it is too high, the spraying area will be too large, wasting slurry, and if it is too low, similar sagging phenomena will easily occur.

[0071] Preferably, in the pinhole repairing process, the spraying of the conductive slurry is intermittent spraying, and the single spraying amount is not higher than 0.5 ml, preferably 0.2 ml, so as to better and more accurately control the amount of conductive slurry filled into the surface of the composite current collector.

[0072] In some embodiments, the flattening of the current collector surface comprises: using a scraper to evenly spread the conductive slurry on the current collector surface;

[0073] The angle between the blade of the scraper and the advancing direction of the current collector is an obtuse angle, preferably 120-140°.

[0074] Among them, the material of the scraper is selected from one or more of titanium, aluminum, stainless steel, PI and other materials with high corrosion resistance, and its average roughness Ra is less than 0.3. At the same time, it forms an obtuse angle with the transmission direction of the composite current collector, such as 135°, and the distance between the scraper and the composite current collector is controlled within 10% of the overall thickness of the composite current collector to ensure that the thickness uniformity of the final product meets the requirements.

[0075] After the surface of the current collector is leveled, the composite current collector needs to be dried to remove volatile organic matter and water in the conductive slurry. The drying temperature is 60-80°C, so that the volatile organic matter and water can escape and evaporate quickly. After the drying process, the composite current collector is cooled to obtain the desired composite current collector, and can also be wound to form a current collector roll for storage, transportation and subsequent processing.

[0076] In some embodiments, the composite current collector is cooled by a water-cooled roller group to achieve online continuous cooling, wherein the water-cooled roller is preferably a water-cooled roller formed by any one or a mixture of stainless steel, high-temperature resistant composite materials, titanium, zirconium and other high-temperature resistant, heat-conductive and corrosion-resistant materials. When multiple water-cooled rollers are used to cool the composite current collector, the distance between the centers of adjacent rollers is set to 0.5 to 1.2 m to ensure sufficient cooling time for the current collector to cool down and avoid adhesion to adjacent film layers after winding.

[0077] In a second aspect, the present application further provides a composite current collector, comprising a resin film layer and metal film layers respectively located on both sides of the resin film layer;

[0078] The metal film layer is partially or entirely covered with a repair layer;

[0079] The repair layer includes a polymer substance and conductive particles distributed in the polymer substance;

[0080] The polymer substance is the same as the resin in the resin film layer or is a derivative of the resin in the resin film layer, such as polyaniline, polypropylene, PET (polyethylene terephthalate), PI (polyimide);

[0081] The conductive particles account for 0.1 to 15% by mass in the repair layer.

[0082] In some embodiments, the conductive particles are at least one of metal, conductive compound of metal, graphene, carbon nanotube, conductive polymer material; and / or

[0083] The particle size of the conductive particles is D90≤10nm, and the specific surface area is ≥2m 2 / g.

[0084] In some embodiments, the thickness of the resin film layer is not higher than 100 μm; and the thickness of the metal film layer is not higher than 10 μm.

[0085] In some embodiments, the diameter of the pinholes on the surface of the composite current collector is no greater than 5 μm.

[0086] In some embodiments, the composite current collector is prepared using the above-mentioned composite current collector preparation method.

[0087] In a third aspect, the present application further provides a battery, comprising a composite current collector, wherein the composite current collector is a composite current collector prepared by the above-mentioned method for preparing the composite current collector.

[0088] In a fourth aspect, the present application further provides an electrical device comprising the lithium-ion battery described in the third aspect.

[0089] In order to facilitate those skilled in the art to better understand and implement the composite current collector provided in the present application, a system for repairing pinholes in the composite current collector is also provided in the present application. Figure 1 , including the following settings:

[0090] A detection device, used to detect pinholes on the surface of the current collector and obtain the coordinates of the pinholes;

[0091] A marking device for marking pinholes on the surface of the current collector according to the detection results and coordinates of the detection device;

[0092] A spraying device for spraying a conductive slurry for repairing pinholes onto the marked portion of the current collector; and

[0093] The flattening equipment makes the conductive slurry sprayed on the current collector evenly cover the surface of the current collector.

[0094] Wherein, the detection device 10 may be a CCD camera, the detection accuracy of which may be 0.05 mm / pixel or above, and the minimum detectable pinhole diameter may be 1 μm or above;

[0095] The marking device 20 includes a first liquid storage mechanism, a first nozzle connected to the first liquid storage mechanism, and a first driver electrically connected to the first nozzle; the first driver receives a marking instruction sent by the controller according to the detection result and the coordinates, and moves the first nozzle to the top of the pinhole to be marked according to the instruction, extracts the liquid for marking, such as a fluorescent agent or a dye, from the first liquid storage mechanism, and sprays it around the detected pinhole to form a marking circle;

[0096] The spraying equipment 30 includes a detector, a second liquid storage mechanism, a second nozzle connected to the second liquid storage mechanism, and a second driver electrically connected to the second nozzle; the detector detects the marking circle on the current collector and collects the coordinates and range of the marking circle; the second driver receives the coordinates and range information of the marking circle obtained by the controller, and sends a repair instruction to the second driver. The second driver moves the second nozzle to the top of the marking circle according to the instruction, extracts the conductive slurry used for repair from the second liquid storage mechanism, and sprays it within the range of the marking circle; during this process, the detector monitors in real time whether the marking circle on the current collector (through the fluorescence or color reflected by the marking circle) is completely covered, and controls the spraying end point of the second nozzle.

[0097] The leveling device 40 includes a third drive and a scraper assembly electrically connected to the third drive, and the third drive drives the scraper assembly to move and rotate longitudinally to adjust the vertical distance from the blade of the scraper in the scraper assembly to the surface of the collector and the angle between the inclination direction of the scraper and the travel direction of the collector.

[0098] The system also includes a drying device 50, a cooling device 60 and a winding device 70 which are sequentially arranged downstream of the leveling device 40, wherein the drying device 50 is used to dry the current collector 110 to volatilize the volatile substances in the conductive slurry to form a solid film layer with good adhesion; the cooling device 60, such as a water-cooled conveyor roller, is used to cool the dried current collector 110 to a lower temperature, such as room temperature, and then roll it into a current collector roll through the winding device 70 to facilitate subsequent transportation, storage and reprocessing.

[0099] In the system, the controller is communicatively connected with the detection device 10 , the marking device 20 , the spraying device 30 , the leveling device 40 , the drying device 50 , the cooling device 60 and the winding device 70 .

[0100] In order to facilitate those skilled in the art to understand the innovative features of the composite current collector and its preparation method, battery, and electrical equipment provided in the present application, some preferred embodiments are provided below in conjunction with the accompanying drawings to illustrate the above technical solutions.

[0101] Example 1

[0102] This embodiment provides a method for preparing a composite current collector, comprising the following steps:

[0103] Step 1: Take 15g of nano copper powder (D90: 10nm, BET: 2m 2 / g), 110g polyaniline, and add 50g pure water, and disperse by ultrasonic vibration for 30min to obtain a conductive slurry with a viscosity of 500cP and a conductivity of 1.2S / cm, which is set aside; 10g potassium iodide (KI) is taken and prepared with 90g pure water into a dyeing solution with a concentration of 0.1g / mL as a dye for marking, which is set aside;

[0104] Step 2: Unwind the PP double-sided copper-plated current collector roll that has formed a "sandwich" sandwich structure at a line speed of 10m / min in an environment with an ambient temperature of 25°C and a humidity of 60%, and use a conveyor roller to convey it to a CCD detection device (detection width 600mm). The detection limit of the detection device is 1μm (accuracy is 0.05mm / pixel), and the coordinates and size of the pinholes with a diameter greater than the set size (such as 5μm) are recorded. The marking device obtains the coordinates of the pinholes, and marks the pinholes with a fluorescent agent according to the coordinates and size of the pinholes to form a marking circle;

[0105] Step 3: The information collection device on the spraying equipment, such as a photosensor, captures the marking circle, and sprays the conductive slurry onto the current collector according to the marking circle, forming a dyeing area with a distance of less than 2 mm at the edge of the pinhole. The spraying pressure is 0.5 MPa, and the vertical distance between the nozzle and the current collector surface is 40 mm. Then, a scraper (material: stainless steel, surface roughness: Ra 0.2, and an angle of 135° with the conveying direction of the current collector) is used to scrape the conductive slurry on the current collector flat;

[0106] Step 4: Then dry at 70°C, and the overall length of the drying equipment is 5m; the dried current collector is cooled by a water-cooled conveying roller and conveyed to a winding chamber, and wound on the winding roller to obtain a composite current collector roll.

[0107] Example 2

[0108] This embodiment also provides a method for preparing a composite current collector. Compared with Example 1, the conductive particles used in step 1 of this embodiment are 5g of nanographene + 10g of nanocopper powder, D90: 5nm, BET: 3m 2 / g, the viscosity of the conductive slurry is 500cp, the conductivity is 2S / cm, and the remaining preparation steps are the same as those in Example 1 to obtain a composite current collector roll.

[0109] Example 3

[0110] This embodiment also provides a method for preparing a composite current collector. Compared with Example 1, a dispersant: sodium dodecylbenzene sulfonate and a wetting agent: ethoxylated fatty acid ester (MEE) are further added in step 1 in this embodiment, wherein the amount of the dispersant added is 8 g, the amount of the wetting agent added is 10 g, the viscosity of the conductive slurry is 400 cp, and the conductivity is 1.6 S / cm. The remaining preparation steps are the same as in Example 1 to obtain a composite current collector roll.

[0111] Example 4

[0112] This embodiment also provides a method for preparing a composite current collector. Compared with Example 3, the amount of conductive particles added in step 1 of this embodiment is 10g nanographene + 20g nanocopper powder, D90: 5nm, BET: 3m 2 / g, the viscosity of the conductive slurry is 300cp, the conductivity is 3S / cm, and the remaining preparation steps are the same as those in Example 3 to obtain a composite current collector roll.

[0113] Example 5

[0114] This embodiment also provides a method for preparing a composite current collector. Compared with Example 4, the scraper used in step three of this embodiment is made of stainless steel with a surface roughness of Ra 0.1 and an angle of 150° with the current collector transmission direction. The remaining preparation steps are the same as those in Example 4 to obtain a composite current collector roll.

[0115] Example 6

[0116] This embodiment also provides a method for preparing a composite current collector. Compared with Example 5, the polymer material used in step 1 of this embodiment is polypropylene (PP), and the remaining preparation steps are the same as those of Example 5 to obtain a composite current collector roll.

[0117] Comparative Example 1

[0118] Compared with Example 3, no conductive particles are added to the conductive slurry in this comparative example, the viscosity is 100 cp, the conductivity is 0.4 S / cm, and the remaining steps are the same as Example 1 to obtain a comparative sample.

[0119] Comparative Example 2

[0120] Compared with Example 3, no polymer substance is added to the conductive slurry in this comparative example, the viscosity is 20 cp, the conductivity is 5 S / cm, and the remaining steps are the same as those in Example 1 to obtain a comparative sample.

[0121] Comparative Example 3

[0122] Compared with Example 3, pure water is not added in step 1 of this embodiment, the viscosity of the conductive slurry is 800 cp, the conductivity is 2.5 S / cm, and the remaining preparation steps are the same as those of Example 4 to obtain a composite current collector roll.

[0123] Comparative Example 4

[0124] This embodiment also provides a method for preparing a composite current collector. Compared with Example 3, the spraying pressure used in step three of this embodiment is 0.05 MPa, the vertical distance between the nozzle and the current collector surface is 300 mm, and the remaining preparation steps are the same as Example 3 to obtain a composite current collector roll.

[0125] Comparative Example 5

[0126] This embodiment also provides a method for preparing a composite current collector. Compared with Example 3, the spraying pressure used in step three of this embodiment is 1 MPa, the vertical distance between the nozzle and the current collector surface is 100 mm, and the remaining preparation steps are the same as Example 3 to obtain a composite current collector roll.

[0127] In addition, a current collector that has not undergone the pinhole detection process and the pinhole repair process, that is, the current collector unwound in Example 1, is used as a control sample.

[0128] test

[0129] 1. Pinhole quantity detection

[0130] Three samples with a size of 300 mm×300 mm were selected from the composite current collector rolls, and the pinhole tester was used to test the samples of the above embodiments, and the number of pinholes and the maximum diameter of the pinholes were recorded;

[0131] 2. Conductivity test

[0132] The sheet resistance of the composite current collector roll sample is tested by a four-probe resistance tester. When wrinkles, pinholes, and other defects appear on the current collector surface, the conductivity will decrease and the sheet resistance will increase accordingly.

[0133] 3. Mechanical properties test

[0134] Three samples with a size of 13 mm × 254 mm were prepared in the horizontal and vertical directions of the above composite current collector roll sample. The two ends of the sample were clamped by a universal mechanical testing machine, exposing a test area of ​​100 mm in length. The test was carried out at a tensile speed of 50 mm / min. MD and TD were along the length direction and width direction respectively. The data obtained are shown in the following table.

[0135] The composite current collector rolls obtained in Examples 1 to 8, the comparative samples and the control samples obtained in Comparative Examples 1 to 3 were respectively subjected to the above tests, and the test results are shown in Table 1.

[0136] Table 1

[0137]

[0138]

[0139] It can be seen from Table 1 that when the viscosity of the conductive slurry is too high or too low, the number of pinholes after repair is still large. This may be because the slurry cannot form a stable and uniform repair layer at the pinholes, and the repair structure formed by the slurry has poor adhesion to the composite current collector. In the subsequent use of the current collector in the battery production process, it may fall off or crack, resulting in an unclear decrease in resistance and limited optimization of strength and elongation at break, such as Comparative Examples 2 and 3.

[0140] Optimally, after further adding a wetting agent and a dispersant to the conductive slurry, the dispersibility of the conductive particles and the leveling of the conductive slurry on the surface of the composite current collector can be better improved, the flatness of the filling structure can be improved, and the resistance, strength, and elongation at break can be optimized more significantly. In addition, the roughness of the scraper surface will also have a certain effect on the filling effect. The lower the roughness, that is, the smoother the surface, the better the repair effect and will not affect the subsequent appearance, as shown in Example 5. More preferably, after adding the same material or derivative as the resin film layer to the conductive slurry, the repair film layer has a good bonding force with the original composite current collector layer and a good repair effect, as shown in Example 6.

[0141] Among them, the polymer material is preferably polyaniline, which has high electrical activity, special electrical and optical properties, and can have conductivity and electrochemical properties after doping. When nano copper powder is added, the conductivity is improved, as in Example 1; when graphene powder is continued to be added and the particle size is reduced, the conductivity is better, as in Examples 2 and 4; when a wetting agent and a dispersant are added, the uniformity is improved, which is also conducive to improving the conductivity, as in Example 3.

[0142] In addition, it can be seen from Comparative Examples 4 and 5 that when the spraying pressure is too high or too low, base film damage, slurry splashing or sag may occur during the filling process of the pinholes, and a good repair effect cannot be achieved;

[0143] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a composite current collector, characterized in that: The following steps are involved: Providing a current collector including a resin film layer and a metal film layer; Inspect the surface of the current collector and mark the location of the pinholes; According to the marked positions of the pinholes, the conductive slurry is sprayed and filled, the surface of the current collector is leveled, and the current collector is dried to obtain a composite current collector.

2. The method for preparing a composite current collector according to claim 1, characterized in that: The viscosity of the conductive slurry is not higher than 1000 cP, and the conductivity is not lower than 1 S / cm.

3. The method for preparing a composite current collector according to claim 2, characterized in that: The conductive slurry comprises a polymer substance and conductive particles, wherein the polymer substance is at least one of the resin in the resin film layer and its derivatives; and / or The conductive particles are at least one of metal, conductive compound of metal, graphene, carbon nanotube, and conductive polymer material; and / or The particle size of the conductive particles is D90≤10nm, and the specific surface area is ≥2m 2 / g.

4. The method for preparing a composite current collector according to claim 3, characterized in that: The conductive slurry further comprises at least one of pure water, a dispersant and a wetting agent; and / or The pure water accounts for 0 to 30% by mass in the conductive slurry; and / or The proportion of the dispersant in the conductive slurry is 0 to 5% by mass; and / or The wetting agent accounts for 0 to 5% by mass in the conductive slurry; and / or The polymer substance accounts for 50-60% by mass in the conductive slurry; and / or The conductive particles account for 0.1 to 15% by mass in the conductive slurry; and / or The pure water is pure water with a conductivity of less than 20 μS / cm; and / or The dispersant is an anionic surfactant or a cationic surfactant; and / or The wetting agent is at least one of a fatty acid wetting agent, an aliphatic amide wetting agent, and a lipid wetting agent.

5. The method for preparing a composite current collector according to any one of claims 1 to 4, characterized in that: In the spraying and filling of the conductive slurry, the conductive slurry is directly opposite to the marked pinhole, the spraying pressure of the conductive slurry is 0.1-0.5 MPa, and the vertical distance between the nozzle and the metal film layer is 150-300 mm.

6. The method for preparing a composite current collector according to claim 5, characterized in that: The conductive slurry is sprayed intermittently, and the single spraying amount is no more than 0.5 ml.

7. The method for preparing a composite current collector according to claim 1, characterized in that: The flattening of the current collector surface comprises: using a scraper to evenly spread the conductive slurry on the current collector surface; The angle between the blade of the scraper and the advancing direction of the current collector is greater than 90°.

8. The method for preparing a composite current collector according to claim 1, characterized in that: When marking the position of the pinhole, any one of a fluorescent agent, a colorant, and a dye is used to mark the position of the pinhole.

9. The method for preparing a composite current collector according to claim 1, characterized in that: In the pinhole detection process, CCD is used to detect pinholes on the surface of the current collector online.

10. A composite current collector, characterized in that: It includes a resin film layer and metal film layers respectively located on both sides of the resin film layer; The metal film layer is partially or entirely covered with a repair layer; The repair layer includes a polymer substance and conductive particles distributed in the polymer substance; The polymer substance is the same as the resin in the resin film layer or is a derivative of the resin in the resin film layer; The conductive particles account for 0.1 to 15% by mass in the repair layer.

11. The composite current collector according to claim 9, characterized in that: The conductive particles are at least one of metal, conductive compound of metal, graphene, carbon nanotube, and conductive polymer material; and / or The particle size of the conductive particles is D90≤10nm, and the specific surface area is ≥2m 2 / g.

12. The composite current collector according to claim 10, characterized in that: The thickness of the resin film layer is not higher than 100 μm; the thickness of the metal film layer is not higher than 10 μm.

13. The composite current collector according to claim 10, characterized in that: The pinholes on the surface of the composite current collector are no larger than 5 μm.

14. The composite current collector according to any one of claims 10 to 13, characterized in that: The composite current collector is prepared by the method for preparing the composite current collector according to any one of claims 1 to 9.

15. A battery, characterized in that: The invention comprises a composite current collector, wherein the composite current collector is a composite current collector prepared by the method for preparing a composite current collector according to any one of claims 1 to 9 or a composite current collector according to any one of claims 10 to 14.

16. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 15.